Investigation of Effects of Process Parameters and Insert Geometry on Hard Turning of Steels - Cheema, Manjot Singh (My University, 2011)
Turning of materials having hardness above 50 HRC (Rockwell scale) is known as hard part turning. Due to technological developments in the area of computerised numerically control machines, it very easy to machine precise components. The development of new tool materials is being used to turn the hard materials at high speeds. All this has lead to elimination of grinding process which had longer setup times and hard part turning is the upcoming trend which is much fast and precised. The present study has been done to study the effect of different input parameters on the desired responses on hard turning of different materials. The effect of hardness, material, depth of cut, nose radius, feed and cutting velocity has been evaluated on the machining force, the surface roughness and dimensional deviation. Taguchi’s orthogonal array was used to design the experiment. The effect of all the input parameters on the output responses have been analyzed using the analysis of variance (ANOVA). White layer formation, phase analysis and micro strain developed were also studied. Grey relational analysis and Genetic Algorithms were used to determine the optimum combination of input parameters to get the best result.
ME, MED
Keywords: hard turning, SAE8620, EN31, EN9, GA